Working with Microsoft Office 4.3 - Blissmer, Robert H.; Alden, Roland H. (Boston : Houghton Mifflin, 1995)
Working with computers and Windows. Working with Microsoft Word 6.0. Working with Microsoft Excel 5.0. Working with Microsoft Powerpoint 4.0. Working with Microsoft Access 2.0.
Keywords: Microsoft Office; Microsoft Word; Microsoft Excel; Computer programs; Microsoft Office; Microsoft PowerPoint (Computer file); Microsoft Excel (Computer file); Microsoft Access (Computer file); Business presentations -- Graphic methods -- Computer programs; Microsoft Word; Word processing; Business -- Computer programs; Electronic spreadsheets